Initiation of aberrant DNA methylation patterns and heterogeneity in precancerous lesions of human hepatocellular cancer. Issue 3 (4th March 2017) - Hlady, Ryan A.; Zhou, Dan; Puszyk, William; Roberts, Lewis R.; Liu, Chen; Robertson, Keith D.
ABSTRACT: While intratumor heterogeneity contributes to disease progression, metastasis, and resistance to chemotherapy, it also provides a route to understanding the evolution and drivers of disease. Defects in epigenetic landscapes are intimately linked to pathogenesis of a variety of human diseases, with epigenetic deregulation promoting tumorigenesis. Understanding epigenetic heterogeneity is crucial in hepatocellular carcinoma (HCC), where epigenetic alterations are frequent, early, and pathogenic events. We determined genome-wide DNA methylation and copy number variation leveraging the Infinium 450K in a series of regenerative nodules from within single patient livers. Bioinformatics strategies were used to ascertain within-patient heterogeneity, link epigenetic changes to clinical features, and determine their relevance to disease pathogenesis. Our data demonstrate that DNA methylation and copy number alterations evolve during the pre-neoplastic phase of HCC and independently segregate regenerative nodules into distinct clusters. Regenerative nodules with a high frequency of epigenetic changes have significantly lower copy number variation, suggesting that individual nodules have differential enrichment of epigenetic and genetic components, with both contributing to disease progression. Regenerative nodules were scored based on 'epigenetic progression' with higher scores associated with increased proliferation measured by Ki67 staining. Early events observed in epigenetically 'aggressive' nodules are enriched for genes involved in liver cancer. Our study demonstrates that marked epigenetic and genetic heterogeneity exists in early pre-neoplastic liver tissue within individual patients, emphasizing the potential contributions of each mechanism to driving liver disease progression, and it unveils strategies for identifying epigenetic drivers of hepatocellular carcinoma.